Enhancing Digital Literacy to Mitigate the Negative Impacts of the Internet among Orphanage Children - Tri Luhur Indayanti Sugata; Tri Puspa Rinjeni; Siti Mukaromah; Virdha Rahma Aulia; Prasasti Karunia Farista Ananto; Rafika Rahmawati; Lano Putra Rajendra; Naufal Hilmy Ramadhani; Rendi Adi Saputra; Arya Daffa Junaidi (Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Pakuan, 2026)
The rapid development of internet technology presents both opportunities and risks for children, particularly those in orphanage settings who face compounded vulnerabilities due to limited supervision and inadequate digital guidance. This community service activity aimed to improve digital literacy and internet safety awareness among children at Al Jabbar Orphanage, Surabaya. This activity involved 13 participants. The program was implemented through three sequential stages: planning, implementation, and evaluation. Data were collected using pre-test and post-test instruments around eight digital literacy indicators covering topics such as understanding internet functions, recognising negative impacts, personal data protection, cyberbullying awareness, account security and information verification. Among the eight indicators assessed, descriptive analysis revealed improvement in two indicators: risk mitigation skills when interacting with strangers online (84.62% to 92.31%) and information verification proficiency (92.31% to 100%). The remaining six indicators showed no measurable change, largely due to high baseline scores. The activity showed potential to improve participants' awareness and understanding of safe internet use, particularly regarding online stranger interactions and information verification. However, given the small sample size and the absence of inferential statistical analysis, stronger evaluation methods are needed to assess the long-term effectiveness of similar programs.